The Effect of Financial Appreciation and Audit Knowledge on Interest in Becoming an Auditor - Yogi Ginanjar; Melia Wida Rahmayani; Ira Rohiliyah (Finance and Business Management Journal, 2024)
This study explores the influence of financial incentives and audit knowledge on accounting students' desire to decide to become auditors. The study involved 126 students from Majalengka University who had completed the audit course. The data collection method utilized a questionnaire along with purposive sampling technique. The results of the analysis revealed that financial incentives and audit skills significantly affected students' desire for the auditor profession. This finding supports expectancy theory, which suggests that financial incentives play a crucial role in one's career choice. In addition, better audit knowledge enhances students' understanding of the roles, responsibilities, and career opportunities in auditing, thus increasing their interest. Overall, this study highlights the importance of financial rewards and audit knowledge in shaping accounting students' interest in becoming auditors. Universities and other relevant stakeholders can gain important insights from the findings of this study as they design ways to increase students' interest in the auditing profession.